The Effect of Avasin Therapy on Cognitive, Executive, and Attention Functions in Adhd Children: A Case Series - Andika Tansir; Gian G. Paramitha; Gita Putri; Vicky Wiharmawan; Deny Hamdani; Suzy Y. Dewi; Harry Rayadi (The Avicenna Medical Journal, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurobehavioral disorder that most commonly occurs in children. The number of ADHD events is getting more increase. Its handling takes a long time so that the use of Complementary Alternative Medicine (CAM) is increasingly in demand. CAM is used by 60-65% of parents with ADHD children to improve symptoms and reduce side effect of conventional medication. Avasin therapy is one the complementary treatments that we used to treat ADHD children.We conducted avasin therapy to 3 children with ADHD. Before and after avasin therapy, the three children were examined by Children's Color Trail Test to access cognitive nd function, BRIEF 2 to access executive function, as well asTOVA and QEEG Brain Mapping to assess attention function.The changes in values on Children's Color Trail Test, nd BRIEF 2 , TOVA, and QEEG Brain Mapping were obtained after a series of avasin therapy.